Anpao : an American Indian odyssey - Highwater, Jamake; Scholder, Fritz, 1937- (Philadelphia : Lippincott, 1977)
Traditional tales from North American Indian tribes woven into one story that relates the adventures of one boy as he grows to manhood.
Bibliography: p. 253-254.
Keywords: Indians of North America -- Folklore; Indians of North America -- Folklore